Sleeve Technique Combined With Aortic Valve Replacement: A Simpler Alternative to the Bentall Procedure. Issue 1 (January 2021) - De Cicco, Giuseppe; Tagliari, Ana Paula; Di Matteo, Gerardo; Trinca, Francesco; Rosati, Fabrizio; Benussi, Stefano
Aortic root disease can be treated with different surgical techniques. The surgical approach of choice depends on patients' comorbidities and aortic valve conditions. We describe an operation combining a Sleeve aortic rootplasty with an aortic valve replacement, as an alternative to the classical Bentall procedure. The patient, a 63-year-old man, was admitted to our institution in April 2019 with severe aortic regurgitation, left ventricle dysfunction (ejection fraction = 44%), and aortic root ectasia (476 mm). Since a sparing aortic valve procedure was judged not feasible because of the thickness and retraction of the leaflets, we decided to perform a procedure through a sleeve operation to treat the aortic ectasia and a standard bioprosthetic aortic valve replacement to treat the aortic regurgitation. The patient had an uneventful postoperative course and was discharged on the sixth postoperative day with aspirin as sole antiplatelet treatment. This procedure may be considered an alternative to the Bentall operation. In fact, it may also offer complete treatment for the aortic root disease, avoiding coronary complications due to coronary ostia manipulation and reimplantation.